Efektifitas Strategi Jigsaw Dan Snowball Throwing Terhadap Hasil Belajar IPA Siswa Kelas IV SDN 3 Jangkungharjo Grobogan Tahun Pelajaran 2016/2017 - Supriyadi, Pebri Dwi, Honest Ummi K, S.S., M. Hum (2017)
This study aims to determine: (1) the difference in the use of Jigsaw with Snowball Throwing strategy on learning outcomes of science in grade IV SDN 3 Jangkungharjo the academic year 2016/2017, (2) the application is better between the use of Jigsaw with Snowball Throwing strategy against results learn science in the fourth grade students of SDN 3 Jangkungharjo the school year 2016/2017. This research is a quantitative experiment. Subjects in this study is the fourth grade students of SDN 3 Jangkungharjo and IV SDN 2 Menduran the academic year 2016/2017. The data collection technique used is the technique of tests and documentation. Test instruments include test the validity and reliability testing. The data analysis technique used is preceded by t test analysis is the prerequisite test for normality and homogeneity test. Based on the results of data analysis with a significance level of 5% obtained t> ttabelyaitu 2.378>2.000 dengan average value of fourth grade science learning outcomes SDN 3 Jangkungharjo greater than the average value of grade IV SDN 2 Menduran ie 80> 76. The conclusion is (1) there are differences in the use of learning outcomes IPA Jigsaw strategy with Snowball Throwing in grade IV SDN 3 Jangkungharjo Grobogan the school year 2016/2017. (2) The learning strategy Jigsaw better than the strategy of Snowball Throwing the learning outcomes of the fourth grade science students at SDN 3 Jangkungharjo Grobogan the school year 2016/2017.